Smart Policing: The Impact Of E-TLE Implementation on Traffic Behavior in South Sumatra, Indonesia - Genda, Erwin Aras; Hakim, Abdul; Noor, Irwan; Setyowati, Endah (Journal of Ecohumanism, 2025)
This study examines the implementation of the Electronic Traffic Law Enforcement (E-TLE) system in South Sumatra, Indonesia, as a means to modernize traffic law enforcement and address longstanding challenges in managing road violations. Grounded in qualitative research, the study explores the technological and human resource dimensions critical to E-TLE's success, including stakeholder collaboration, public compliance, and institutional responsiveness. Using Grindle's policy implementation framework, the research highlights the interplay between policy design, political context, and societal reception, emphasizing the need for robust communication strategies and infrastructural improvements. Findings reveal that while E-TLE has enhanced efficiency in traffic law enforcement, challenges such as public unfamiliarity and resource limitations persist, necessitating targeted interventions to ensure sustained success.